Optimizing the Potential of Early Childhood Students at TK Kemala Bhayangkari 14 Through Educational Garden Based on PAR - Putri, Sovia Ikhwani; Bahagia, Siti Nur; Nasution, Ilmi Hamidah; Lubis, Annisah; Anggraini, Pradika Dwi; Nasution, Melda Diana (Help: Journal of Community Service, 2025)
Early childhood education necessitates interactive learning approaches to foster holistic development. Educational gardens have been recognized as effective learning tools that provide hands-on experiences. This study employs a Participatory Action Research (PAR) approach to examine the impact of an educational garden at TK Kemala Bhayangkari 14 on early childhood students. Data were collected through observations, interviews, and participatory assessments. Findings indicate that the educational garden significantly enhances cognitive, social-emotional, and physical development in children. Furthermore, the PAR method effectively engages educators, parents, and students, fostering collaborative learning experiences. Challenges identified include sustainability concerns and resource limitations. The study underscores the importance of integrating educational gardens in early childhood education. Sustainable implementation requires strategic planning, community involvement, and institutional support. Future research should focus on longitudinal impact assessments and digital enhancements to garden-based learning.